The Early Childhood Educator: A Career of choice beyond the 21st century in Africa - Chepsiror, Philomena (Aulad: Journal on Early Childhood, 2020)
Sustainable Development Goal 8 calls for full, freely chosen and productive employment and decent work for all. However, Evidence from statistics shows that employment opportunities have continued to diminish world over and that the shortage of jobs is expected to continue in the near future. Africa bears the brunt for this unemployment situation. The good news however, is that early childhood education (ECE) in Africa is growing in leaps and bounce and is expected to continue growing as awareness around it intensifies. Findings from a critical analysis of pertinent literature, indicate that the rising realization of the importance of ECE, the growing population, improved perception of ECE, professionalization of the ECE educator, in addition to mainstreaming, advocacy and positioning of ECE as a priority in national development agendas is evidence that development in the early childhood education might be the magic bullet for the unemployment menace in Africa. The paper was expected to inspire policy makers to step-up investment in early childhood education and mark it as a career of choice for the 21st century and beyond. This review provides an opening toward a broader understanding of the future livelihood chances for an early childhood educator